2007
DOI: 10.1007/s11259-007-9029-3
|View full text |Cite
|
Sign up to set email alerts
|

In vitro reactivity and growth inhibition of EPEC serotype O111 and STEC serotypes O111 and O157 by homologous and heterologous chicken egg yolk antibody

Abstract: IgY is a chicken egg yolk antibody which has been used for treatment and prophylaxis of gastrointestinal infections. Our aim was to verify if IgY obtained from chickens immunized with EPEC O111, STEC O111 and STEC O157 is able to show in vitro reactivity and biological activity towards the three bacteria. IgY was obtained from eggs laid before and after immunization with each bacterium. The preparations of IgY anti-EPEC O111 and anti-STEC O111 shared high reactivity detected by ELISA and growth inhibition abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 29 publications
2
17
1
Order By: Relevance
“…Figures 2 to 9 demonstrated the inhibition of cell growth of all staphylococcal cells used. The results of growth inhibition of E. coli from different sources were also observed by others by using IgY from chicken in vivo and in vitro assays (4, 33) and their therapeutic potential was suggested. Effects of IgY antibodies from chicken against E.coli strains conferring protection against gastrointestinal infections in different species as a food additive component (14), for treatment of diarrheic calves (18) and piglets (16, 22) were demonstrated.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…Figures 2 to 9 demonstrated the inhibition of cell growth of all staphylococcal cells used. The results of growth inhibition of E. coli from different sources were also observed by others by using IgY from chicken in vivo and in vitro assays (4, 33) and their therapeutic potential was suggested. Effects of IgY antibodies from chicken against E.coli strains conferring protection against gastrointestinal infections in different species as a food additive component (14), for treatment of diarrheic calves (18) and piglets (16, 22) were demonstrated.…”
Section: Resultssupporting
confidence: 62%
“…coli (EPEC), enteroinvasive E. coli (EIEC), enterohemorragic E. coli (EHEC), enteroagregative E. coli (EAEC) and extraintestinal patogenic E. coli (EXPEC) are among the causes of diarrhea in human and animal leading to economic loss for farmers, including birds and mammals (18). Antibodies developed against several microorganisms in chickens, also known as IgY, has been proved to be an alternative for immunological diagnostic tool, as well as suggested as immunotherapic purposes (4, 12, 13, 15, 17, 21, 31). The aim of this work was to demonstrate for the first time the inhibitory activity of polyclonal antibodies developed in ostriches against recombinant proteins recRAP and recSEC from S. aureus and recBFPA and recEspB from E.coli , towards clinical and standard strains of S. aureus and E. coli in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…The chickens were maintained under conventional conditions in the animal room of the Immunology Research Institute, GHEN Corporation (Gifu, Japan). The immunization procedure was approved by the Animal Care and Use Committee of the Institute (approval number; 06- [6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, oral administration of chicken IgY antibody has been demonstrated to prevent or control several intestinal infections. [11][12][13][14] It is more desirable to neutralize Stx in the intestine than in the circulation, although oral administration requires larger quantity of antibodies compared with parenteral administration.Chicken IgY is thought to be an economical source to obtain large amounts of antibody that can be given orally.We previously have demonstrated that immunization with formalin-inactivated Stx-1 and Stx-2 induces Stx-neutralizing IgY antibodies in chickens. 15) Oral administration of IgY protects mice from death caused by intestinal infection with EHEC O157:H7.…”
mentioning
confidence: 99%
See 1 more Smart Citation